Analysis of Needs Response to the Development of Digital Comic on Straight Motion Kinematics Materials - Aulia Nurmalinda Hapsari; Eko Risdianto; Rosane Medriati (CV. Media Inti Teknologi, 2022)
The purpose of this research is to analyze the result of the response to the needs of development digital comics for students. This research is a descriptive research part of R&D research using the ADDIE model. The instruments used are observation sheets, interview sheets, and questionnaire sheets. The subjects consisted of physics teachers and class X students with 147 students and 4 teachers. The instruments used in this study are valid and reliable, students and teachers in 3 high schools in Bengkulu City strongly agree and need digital comic-based learning media with a result obtained being 83,45%.